Suicide by hanging - methodology of proceeding during the examination of the event - Pindel, Piotr (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
Suicide by hanging is a social phenomenon that is very often analyzed by police officers at the place of its disclosure. Activities carried out pursuant to Art. 308 of the Code of Criminal Procedure provide for an inspection of both the place where the corpse was discovered and the examination of the corpse. Both of these activities are classified as procedural activities and a protocol is drawn up for each of them. This article presents the activities carried out by a forensic technician at the scene of the event, aimed at a kind of reconstruction of the event by revealing traces and objects and their proper protection. The role performed by a forensic technician can definitely be considered necessary and his participation can be compared to the participation of a specialist because the conclusions drawn on the basis of his work should be considered key and often constitute the basis for further preparatory proceedings.